Strong mosquitocidal Bacillus thuringiensis from Mt. Everest - Shrestha, Upendra Thapa; Shahukhal, Gyan Sunder; Tiwari, Kiran Babu; Pokhrel, Subarna; Singh, Anjana; Agrawal, Vishwanath Prasad (Our Nature, 2008)
Bacillus thuringiensis strains were isolated from soil samples collected from Khumbu Base Camp of the Everest region and characterized by standard microbiological techniques viz. colonial and morphological characteristics, and biochemical tests. Insect bioassay of each isolate was performed by standard method using mosquito larva. Among ten randomly selected isolates, one isolate showed the highest insecticidal activity against Dipteron insects. Keywords: Insect-bioassay, Isolates, Khumbu region, Mosquitocidal, Mosquito larva doi:10.3126/on.v5i1.800 Our Nature (2007)5:67-69